Adsorptive Treatment of Residues on Macroporous Adsorbent for Marine Fuel Production Scheme on Refinery - Renata Iuzmukhametova; Roman Boldushevskii; Olga Shmelkova; Yunir Khamzin; Artem Minaev; Pavel Nikulshin (Journal of Marine Science and Engineering, 2023)
Adsorptive treatment using granulated macroporous Al2O3-SiO2 adsorbent is proposed as a preliminary stage for residue pretreatment in refineries. The study evaluates the adsorptive treatment of atmospheric and visbreaking residue at 485–510 °C and 1 h−1 feed rate, resulting in a total liquid product yield of about 73.0–75.0 wt%, coke on the sorbent of 12.6–18.3 wt%, demetallization exceeding 98%, and a reduction in carbon residue of 65–72%. The paper also discusses the role of feed dilution with light gasoil, process temperature, and feed rate in optimizing the adsorptive treatment process. The high coke content on the adsorbent necessitates its regeneration, which is shown to be complete at temperatures up to 750 °C. Regeneration decreases macropore size and volume but does not significantly impact demetallization. The pretreated residual product has low viscosity and is further processed through hydrotreatment in a fixed-bed unit to produce low-sulfur marine fuel. The hydrotreated atmospheric residue meets the requirements for RMA 10 fuel, with a sulfur content lower than 0.1 wt%.